Stock Market Anomalies as Mediators Between Prospect Factors and Investment Decisions and Performance: Findings at the Individual Investor Level - Mariam Farooq; Syed Zulfiqar Ali Shah (The Lahore Journal of Business)
While other studies have investigated the direct impact of prospect factors on investment decisions and performance at the individual level, we examine the mediated link between the two, via fundamental, technical and calendar anomalies. The study applies a structural equation model to data for 324 individual investors in Pakistan. Our findings show that two processes, fundamental and calendar anomalies, mediate the relationship between certain prospect factors and investment decisions and performance. Of these prospect factors, regret aversion is the strongest predictor of investment decisions and performance, followed by calendar anomalies. It is also the strongest predictor of investment decisions and performance via fundamental anomalies.